Predictive value of serum and follicular fluid chemerin concentrations during assisted reproductive cycles in women with polycystic ovary syndrome - KABİL KUCUR, SUNA (TAYLOR & FRANCIS LTD, 2021)
Aims To evaluate the effect of serum and follicular fluid (ff) Chemerin levels on Assisted Reproductive Technology (ART) outcomes in lean patients with PCOS. Materials and methods The study included 76 infertile reproductive aged women, between 21-35 years who underwent intracytoplasmic sperm injection (ICSI) procedure. Serum and ff Chemerin levels were evaluated. Fertilization and clinical pregnancy rate were compared between the groups. Results Serum (13.32 ng/ml versus 29.82 ng/ml) and ff chemerin (35.90 ng/ml versus 87.60 ng/ml) levels were significantly higher in lean PCOS patients compared to controls (p < .01). Serum (24.5 ng/ml versus 18.4 ng/ml) and ff chemerin (71.7 ng/ml versus 52.8 ng/ml) levels were higher in subjects without clinical pregnancy compared to the subjects with clinical pregnancy (p < .05). A cutoff value of 36.2 ng/ml in the ff chemerin level was found to estimate clinical pregnancy with 83% sensitivity and 52% specificity (Area under the curve 0.66; 95% confidence interval, 0.53-0.79). A cutoff value of 12.7 ng/ml in the serum chemerin level was found to estimate clinical pregnancy with 91% sensitivity and 49% specificity (Area under the curve 0.65; 95% confidence interval, 0.52-0.78). Clinical pregnancy rates were significantly higher in group with lower serum chemerin levels (80.0% versus 30.4%, p < .001). High serum chemerin levels are associated with failure of assisted reproduction [OR:0.1(95% CI, 0.03-0.4, p < .001)]. Conclusions PCOS is associated with higher serum and ff chemerin levels and high serum chemerin level is a risk factor for failed ART cycle.
Keywords: Chemerin; follicular fluid; infertility; polycystic ovary syndrome; INSULIN-RESISTANCE; PREVALENCE; OBESITY; IMPACT; FAT